METHODS AND SYSTEMS FOR SOCK-LOADING FIXED BED REACTORS (2020)
Provided herein are methods for effectively loading reactor material into fixed bed reactors. The subject methods and systems for loading catalyst particles and inert particles onto a reactor bed utilize a novel sock having a helical-shape that can restrict reactor material traveling through the elevation of the fixed bed reactor to the reactor bed and avoid damaging the reactor material upon impact. The sock comprises a cylindrical tube having a plurality of helixes. Each helix of the cylindrical tube has a downward slope. The downward slope of each helix exceeds an angle of repose of the reactor material. The present methods and system are particularly effective for improving the performance of reactor bed configurations of vertically-oriented fixed bed reactors and flow distribution through the bed at designated operating conditions.